إعادة هيكلة الاقتصاد السوري لدخول اقتصاد السوق ومنظمة التجارة العالمية - العربيد, عدنان; شرف, سمير; عطيرة, عبير سليمان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تناول هذا البحث دواعي انضمام سورية إلى منظمة التجارة العالمية (WTO)، ولذلك تطرقت إلى وجهات نظر كل من معارضي هذا الانضمام ومؤيديه، وكان ذلك في سياق تحديد متطلبات انضمام سورية إلى منظمة التجارة العالمية في المدى القصير والطويل الأجل، ولذلك تم دراسة المتطلبات التالية في المدى القصير الأجل: تحرير المبادلات التجارية من القيود الجمركية، و تطوير القوانين الاقتصادية، وحماية الملكية الفكرية، كل ذلك بهدف تمكن قوانين وآليات السوق المتمثلة بالشفافية والمنافسة من السيطرة على الاقتصاد الوطني، أما المتطلبات التي تم دراستها في المدى طويل الأجل فهي: توحيد أسعار صرف العملة السورية بهدف تعويمها في سياق بناء مؤسسات وآلية اقتصاد السوق(كالأسواق المالية والخصخصة)، وبالتالي الانضمام إلى منظمة التجارة العالمية. كما حاول هذا البحث توضيح مدى الربح أو الخسارة، التي من الممكن أن تنتج عن انضمام سورية إلى منظمة التجارة العالمية، وكذلك معوقات تحول الاقتصاد السوري إلى اقتصاد السوق، ومعوقات انضمامه إلى منظمة التجارة العالمية، وقد توصل البحث إلى نتائج هامة مفادها: أن انضمام سورية إلى منظمة التجارة العالمية، أو غيرها من الشراكات أمر لا مفر منه، فليس هناك مجال أمام سورية إلا أن تقلل الخسائر المحتملة، وأن تغتنم الفرص الجديدة التي يتيحها النظام العالمي الجديد، وتحويل هذه الفرص من نظرية إلى واقعية، وذلك من خلال تأمين متطلبات الانضمام على المدى القصير والطويل، خاصةً تحقق المتطلبات الأكثر أهمية، وهي الشفافية والمنافسة، والتي تجعل الاقتصاد السوري بمستوى الشراكات الدولية، وتضمن له النجاح في الانتقال إلى اقتصاد السوق، وبالتالي الانضمام إلى منظمة التجارة العالمية بأقل التكاليف. This research discusses the reasons for Syria to join the World Trade Organization. I have dealt with the two points of view (opposers and upholders)in sequence of the requirement of Syria joining the (WTO) in short and long terns .It has to complete the following requirement in the short - run : - Releasing the trade exchanges from the customs duties. - Developing the economic laws. - Intellectual ownership protection. All these in order to control of market laws represented by competence and transparency. As for the requirements that have to be studied in the long- extensions they are: - Unifying Syrian Currency exchange in order to float in sequence of constructing the economy market Facilities as Financial private markets in order to join (WTO) . This research also tries to explain the range of winning or losing as result of Syria gining to (WTO). It also identifies the barriers of Syrian economy changing in a market economyand its difficulties of gining to (WTO). This study has reached to an important result which is: - Syria is gining to(WTO) or any other sharing is inevitable, because there is no way for Syria but to decrease the probable loses and to get benefit of the new chances which are exposed by the New International System . Syria has to change these chances from theory to reality through fulfilling the gining requirements for the short and long terms, especially the more important requirements, which are transparency and importance, which raise the performance and enable it to achieve success through moving to market economy and ginning World Trade Organization at a lower price.